Gambar dan Kata: Efektivitas Dual Coding dalam Meningkatkan Long- Term Memory - Mas Bakar, Resekiani; Anugrah, Rahma; Jasmal, Nurul Amaliah; Jannah, Ghaitsa Raodatul (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to examine the effect of the dual coding method on students' long-term memory. A true experimental approach with a between-participant design was employed in this research. The participants consisted of 32 students aged between 13 and 14 years, randomly assigned to two experimental groups (16 students in each group). Long-term memory was assessed using a presentation of concrete nouns. The first experimental group received a combination of words and images, while the second group was presented with words only. To measure long-term memory, students were asked to recall and write down the concrete nouns they had previously seen. Data analysis was conducted using the Mann-Whitney test due to the non-normal distribution of the data. The results revealed that the dual coding method had a significant positive effect on enhancing students’ long-term memory. These findings contribute to the development of instructional strategies that effectively integrate visual and verbal elements to strengthen memory retention.